Adenocarcinomas at different positions at the gastro-oesophageal junction show distinct association with gastritis and gastric preneoplastic conditions. Issue 5 (May 2015) - Bornschein, Jan; Dingwerth, Andrea; Selgrad, Michael; Venerito, Marino; Stuebs, Patrick; Frauenschlaeger, Katrin; Achilleos, Achilleas; Roessner, Albert; Malfertheiner, Peter
<x xml:space="preserve">Abstract</x> Objective Adenocarcinomas at the gastro-oesophageal junction (GOJ) are currently stratified by tumour location. This retrospective study examines the association of preneoplastic conditions and inflammation of the gastric mucosa with GOJ cancer at different locations and compares them with nonjunctional gastric cancers. Patients and methods A total of 520 patients with junctional and nonjunctional gastric cancer were assessed for the presence and degree of intestinal metaplasia, glandular atrophy and inflammation in the stomach. Histopathological data were complete for 428 patients (68.9% men, median age 67.7 years), including 172 patients with GOJ cancer (GOJ1: 1–5 cm proximal to the junction, GOJ2: 'true' junctional, GOJ3: 2–5 cm distal to the junction). Gastric inflammation and preneoplastic conditions were scored according to the updated Sydney classification and further stratified into respective operative link on gastritis assessment (OLGA) and operative link on gastritis assessment on intestinal metaplasia (OLGIM) stages. Results The prevalence and degree of gastric atrophy and intestinal metaplasia were significantly lower in GOJ1 than GOJ3 (P<0.01). Preneoplastic conditions in the stomach were similar in GOJ3 compared with nonjunctional gastric cancer. GOJ1 were almost exclusively (98.4%) of the intestinal type, whereas GOJ2 and GOJ3 were the diffuse type in 22.6 and 22.4% of the patients (P<0.001). Of all patients, only 8.5 and 12.7% presented with stage III/IV according to OLGA and OLGIM, respectively. However, data for OLGA and OLGIM staging were only available in 61.2 and 67.9% of patients, respectively. Conclusion GOJ1 are less likely to be associated with gastric pathology compared with GOJ3 or nonjunctional gastric cancer. OLGA or OLGIM staging in patients with advanced gastro-oesophageal cancer seems to be of limited value.